(untitled) (CIPEEX, 2022)
INTRODUCTION: THE UNITED NATIONS 2030 AGENDA IS COMMITTED TO PROVIDING ACCESS TO JUSTICE FOR ALL. OBJECTIVE: THE OBJECTIVE OF THE PRESENT STUDY WAS TO UNDERSTAND THE CHALLENGE TO EFFECT ACCESS TO JUSTICE THROUGH THE LANGUAGE USED IN COURT DOCUMENTS. MATERIALS AND METHODS: A SEARCH FOR REFERENCES WAS CARRIED OUT IN THE CAPES PERIODICALS AND GOOGLE SCHOLAR DATABASES IN SEPTEMBER 2022. IN A LATER STAGE, THE DATA COLLECTED IN AN INTERVIEW CARRIED OUT IN JUNE 2022 WERE ANALYZED. RESULTS: FROM THE DATA ANALYSIS, IT WAS POSSIBLE TO IDENTIFY THAT ONE OF THE OBSTACLES TO EFFECTIVE ACCESS TO JUSTICE IS OBSCURE LANGUAGE. IN ADDITION, IT WAS FOUND THAT 63.6% OF RESPONDENTS IN A SURVEY RESPONDED THAT THE LANGUAGE USED IN COURT DOCUMENTS SHOULD BE SIMPLER. CONCLUSION: THEREFORE, IT WAS POSSIBLE TO CONCLUDE THAT A LEGAL DOCUMENT MUST HAVE A CLEAR AND SIMPLE LANGUAGE TO EFFECT ACCESS TO JUSTICE.